Literatur review: Analisis Dampak AI bagi Dunia Pendidikan - Firza, Syafiq Azzumar (Jurnal Pelita Teknologi, 2023)
Artificial intelligence is a system developed in research and capable of innovation, mimicking a machine or computer, that has intelligence equal to or greater than humans, that adapts, makes decisions cognitively, and learns. Specifically, we will explore various aspects of education, including management, teaching, and learning, and determine how artificial intelligence will impact education. This research utilizes a retrospective approach technique that consists of collecting data and secondary materials or conducting surveys. We help explain research and development by using, theory, and empirical data to demonstrate and discuss educational approaches that impact artificial information, such as the H-index. The analysis also identifies other important themes and how artificial intelligence will impact teacher work standards and improve academic integrity. Another important finding from various sources is that, as educational resources are now accessible via the Internet, teachers are using the platform to perform certain administrative tasks.